KAJIAN MAANIL HADIS; : POSTUR NABI ADAM AS 60 HASTA DAN POLA KOMUNIKASI ANTAR MAKHLUK - Munadi, Radhie (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2023)
As the first human being, the figure of Prophet Adam as. certainly very curious humans who exist now. However, there is not much literature on the description of this creature that has become the envy of this faction of angels and demons. There are only a few facts about what the first humans looked like. One of them about his height which reached 60 cubits, about the equivalent of 30 meters. This study will examine how the hadith view of the posture of the Prophet Adam As and the pattern of communication between creatures. With the maanil hadith approach, it is hoped that it can provide a new nuance of thinking about the posture of the Prophet Adam As in relation to the current and future human condition.